Transforming Rooftop Terraces to Third Places in Urban India - Sonia Gupta; Suganya Law (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
This research explores the potential of residential rooftop terraces as a ‘third’ place for community activities in urban India, where increasing density has throttled access to open spaces. During the COVID-19 lockdown, usage of shared and private terraces saw a surge and was being used for various purposes. An online survey was conducted to assess the usage types and to understand potential preferences for taking advantage of this largely underused resource. Response from across India within varied age groups and types of terrace users indicated opportunities for more than socialising, amidst passively cooled roofs. Almost all who had access to a roof terrace wanted to use the space in a manner that is inclusive and engaging for the residential community. Formulation of recommendations, based on this community aspiration and sharing with building permit authorities, is one of the outcomes of this study.